2013
DOI: 10.1371/journal.pone.0073232
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effect of Mast Cell Stabilizers Ketotifen and Tranilast on the Vasoconstrictor Response to Electrical Field Stimulation in Rat Mesenteric Artery

Abstract: ObjectivesWe analyzed whether mast cell stabilization by either ketotifen or tranilast could alter either sympathetic or nitrergic innervation function in rat mesenteric arteries.MethodsElectrical field stimulation (EFS)-induced contraction was analyzed in mesenteric segments from 6-month-old Wistar rats in three experimental groups: control, 3-hour ketotifen incubated (0.1 αmol/L), and 3-hour tranilast incubated (0.1 mmol/L). To assess the possible participation of nitrergic or sympathetic innervation, EFS co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 35 publications
(50 reference statements)
4
14
1
Order By: Relevance
“…This was confirmed by the fact that NO release, superoxide anion formation and vasodilator response to NO donor DEA-NO were not modified after preincubation with tranilast, similarly to reported in rat aorta [15]. All these results contrast with our previous results in superior mesenteric artery, where we observed decreases in neuronal NO and superoxide anion releases and an increase in the vasodilator response to DEA-NO after tranilast preincubation [14]. In conclusion, the results obtained in the present study confirm the fact that the increased vasodilator response to ACh produced by tranilast is not due to modifications in the NO pathway.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This was confirmed by the fact that NO release, superoxide anion formation and vasodilator response to NO donor DEA-NO were not modified after preincubation with tranilast, similarly to reported in rat aorta [15]. All these results contrast with our previous results in superior mesenteric artery, where we observed decreases in neuronal NO and superoxide anion releases and an increase in the vasodilator response to DEA-NO after tranilast preincubation [14]. In conclusion, the results obtained in the present study confirm the fact that the increased vasodilator response to ACh produced by tranilast is not due to modifications in the NO pathway.…”
Section: Discussionsupporting
confidence: 91%
“…In this study we have located perivascular mast cells around mesenteric resistance vessels, as has been described in superior mesenteric artery [14]. Previously, we have described that tranilast decreases EFS-induced vasoconstriction in superior mesenteric arteries [14]. Since total peripheral resistance mainly depends on resistance vessels, and the role that mesenteric resistance arteries play in this is very relevant, we consider it very important to analyze the possible alterations tranilast may produce in the endothelial function of these vessels.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…), mast cell stabilization (Sastre et al. ), and modulation of tryptophan metabolism (Munn et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…However, later studies using human conjunctival mast cells additionally revealed a mast cell-stabilizing property of ketotifen [7,8], consistent with its higher potency in the treatment of allergic disorders. So far, by measuring the amount of chemokines released from rat peritoneal mast cells, such as histamine and β-hexosaminidase, previous studies have suggested the superiority of ketotifen to tranilast in the properties of mast cell stabilization [9][10][11]. However, due to the limitations of the methods used in molecular biology [12], the effects of these drugs on the exocytotic process of mast cells have not directly been examined.…”
Section: Introductionmentioning
confidence: 99%